Petrography and geochemistry of dolomites of samanasuk formation, Dara Adam khel section, Kohat ranges, Pakistan - Khan, Emad Ullah; Naseem, Abbas Ali; Saleem, Maryam; Rehman, Faisal; Sajjad, Syed Waseem; Ahmad, Waqar; Azeem, Tahir (Penerbit Universiti Kebangsaan Malaysia, 2021)
Replacement dolomite occurs in Jurassic Samanasuk Formation in Dara Adam khel area of Kohat ranges, North-Western Himalayas, Pakistan. This study, for the first time, document the process of dolomitization and evolution of strata bound dolomitic bodies. Field investigation, petrography and geochemistry helped in unraveling the formation of several dolomitic bodies. Petrographically dolomites comprises of: (1) medium grain crystalline planer subhedral dolomite (Dol-I); (2) fine grained crystalline anhedral non-planer dolomite rhombs (Dol-II); (3) medium to coarse grained crystalline subhedral-anhedral non-planer dolomite (Dol-III) and coarse to very coarse grained crystalline saddle dolomite cements (SD). The saddle dolomites (SD) postdate the replacement dolomites and precede telogenetic calcite (TC) cements. Stable O and C isotope analysis shows that these dolomites have δ18Ovpdb ranging from -4.09% to -10.4 whereas the δ13Cvpdb ranges from +0.8 to +2.51. Major and trace elements data show that Sr concentrations of 145.5 to 173 ppm; Fe contents of 2198 to 8215 ppm; and Mn contents of 93.5 to 411 ppm. Petrographically replacive dolomites, saddle dolomite, and δ18Ovpdb values depicts neomorphism of replacement dolomites that were formed earlier were exposed to late dolomitizing fluids. As a result of basin uplift during the Himalayan orogeny in Eocene time, dolomitization event was stopped through occurrence of meteoric water. The Main Boundary Thrust (MBT) and its splays were most likely essential conduits that channelized dolomitizing fluids from siliciclastic rocks that were buried deeply into the Jurassic carbonates rocks, leading to more extreme dolomitization.